Genetic analysis of Stellate elements of Drosophila melanogaster. - Palumbo, G.; Bonaccorsi, S.; Robbins, L.G.; Pimpinelli, S. (Genetics, 1994)
Repeated elements are remarkably important for male meiosis and spermiogenesis in Drosophila melanogaster. Pairing of the X and Y chromosomes is mediated by the ribosomal RNA genes of the Y chromosome and X chromosome heterochromatin, spermiogenesis depends on the fertility factors of the Y chromosome. Intriguingly, a peculiar genetic system of interaction between the Y-linked crystal locus and the X-linked Stellate elements seem to be also involved in male meiosis and spermiogenesis. Deletion of the crystal element of the Y, via an interaction with the Stellate elements of the X, causes meiotic abnormalities, gamete-genotype dependent failure of sperm development (meiotic drive), and deposition of protein crystals in spermatocytes. The current hypothesis is that the meiotic abnormalities observed in cry- males is due to an induced overexpression of the normally repressed Ste elements. An implication of this hypothesis is that the strength of the abnormalities would depend on the amount of the Ste copies. To test this point we have genetically and cytologically examined the relationship of Ste copy number and organization to meiotic behavior in cry- males. We found that heterochromatic as well as euchromatic Ste repeats are functional and that the abnormality in chromosome condensation and the frequency of nondisjunction are related to Ste copy number. Moreover, we found that meiosis is disrupted after synapsis and that cry-induced meiotic drive is probably not mediated by Ste.